2009
DOI: 10.1080/00103620802646852
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Parameters of Infectivity and Efficiency of DifferentGlomus mosseaeArbuscular Mycorrhizal Fungi Strains in Cadmium‐Loaded Soils

Abstract: Adaptability of five Glomus mosseae cultures of different origins to the soil cadmium (Cd) content and the changes of the efficiency of the symbiosis between the arbuscular mycorrhizal fungi (AMF) strains and white clover (Trifolium repens L.) hosts were investigated in a pot experiment. The parameters of mycorrhizal colonization of the different strains and efficiency such as macroand microelement content of the shoots of mycorrhizal and nonmycorrhizal plants, the plant growth response to the increasing soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Within three Glomus species, intraspecific variation in AM fungal growth (extraradical hyphal production) and symbiotic functioning (phosphorus uptake and host plant growth parameters) was observed by Munkvold et al (2004). Functional variation in nutrient uptake and response to heavy metal contamination was observed among isolates of Glomus mosseae (Biró & Takács 2007;Biró et al 2009). As these responses were evaluated in 'common garden' studies, differences among isolates may have been attributable to the intrinsic fitness and symbiotic capacity of each isolate and/or variable responses to the environment in which they were grown (in terms of the host plant or the abiotic conditions).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within three Glomus species, intraspecific variation in AM fungal growth (extraradical hyphal production) and symbiotic functioning (phosphorus uptake and host plant growth parameters) was observed by Munkvold et al (2004). Functional variation in nutrient uptake and response to heavy metal contamination was observed among isolates of Glomus mosseae (Biró & Takács 2007;Biró et al 2009). As these responses were evaluated in 'common garden' studies, differences among isolates may have been attributable to the intrinsic fitness and symbiotic capacity of each isolate and/or variable responses to the environment in which they were grown (in terms of the host plant or the abiotic conditions).…”
Section: Discussionmentioning
confidence: 97%
“…(2004). Functional variation in nutrient uptake and response to heavy metal contamination was observed among isolates of Glomus mosseae (Biró & Takács 2007; Biró et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…to nodules which may be another strategy whereby AM fungi alleviate the detrimental effects of stresses. Kaya et al (2009), Biro et al (2009 and Janouskova and Pavlikova (2010) suggested that Na ? and Cd 2?…”
Section: 05) As Determined By Dunnett's Multiple Comparison Testmentioning
confidence: 99%
“…Our results of F. mosseae -pigeonpea relationship proved that AM fungus was functionally active in Cd or Zn polluted soils, suggesting that the fungal symbiont could thrive under the experimental metal concentrations. Under heavy metal stress, AM initiates the formation of spore forming hypha, resulting in rapid production of spores, which could be a mechanism for AM metal endurance (Biró, Nemeth, & Takács, 2009;Helgason & Fitter, 2009). Metal-induced decrease in MC has been documented in literature, nevertheless, metal tolerant fungal ecotypes and mycorrhizal colonized plants are found growing in metal contaminated soils (Hidelbrant, Regvar, & Bothe, 2007).…”
Section: Discussionmentioning
confidence: 99%